The sensitivity of the SERVQUAL score to the choice of the fuzzy conversion scale - Jefmański, Bartłomiej (Wrażliwość wskaźnika SERVQUAL na wybór rozmytej skali konwersji, 2017)
The Fuzzy SERVQUAL method enables to assess the service quality when the measurement results of the performance perception and expectations are expressed in the form of fuzzy numbers. The measurement results expressed in the form of fuzzy numbers are the results of applying the fuzzy conversion scales which are the most popular form of fuzzy scales. Fuzzy conversion scales assume that their points are expressed in the form of fuzzy numbers. The choice of fuzzy number parameters which describe the various points of measurement scales is most often subjective. The aim of the article is to assess the impact of the choice of the fuzzy conversion scale on the stability of the assessment results of the ser-vice quality using the fuzzy SERVQUAL method. The stability assessment was made both for the individual dimensions and the overall SERVQUAL score. The results of employee satisfaction surveys of the West Pomeranian Province local government were used for the purpose of the assessment. The results suggest that there is no significant impact of the form of fuzzy conversion scales on the stability of the assessment results of the service quality us-ing the fuzzy SERVQUAL method
Ekonometria = Econometrics, 2017, Nr 3 (57), s. 59-71
Keywords: fuzzy sets; fuzzy numbers; fuzzy scales; fuzzy SERVQUAL; zbiory rozmyte; liczby rozmyte; skale rozmyte; rozmyty SERVQUAL